Faktor Psikologis yang Mempengaruhi Perilaku Merokok pada Remaja - Wulan, Dwi Kencana (Bina Nusantara University, 2012)
Smoking behavior can be classified as the cause of danger deaseas, both for smokers and for others around them. Smoking is shown to be associated with 25 types of disease that is deadly dangerous, such as lung cancer and coronary heart disease. Every year, deaths caused by smoking increas, but the number of smokers also increases. However, the beginning of a person's age smoking is getting younger. Teenagers reach a high figure as the beginning of a person's age smoking. The reasons for teenagers to smoke tend to be psychosocial. Researcher wants to know what factors play a role in smoking behavior in adolescents. The research method used is descriptive research, that aims to obtain an overview of the factors that play a role in smoking behavior in adolescents. The characteristics of samples: 11-18 years old, still smoking at the time of data retrieval. A measuring tool used is based on the concept of adolescent development from Hurlock. Obtained result is the most instrumental factor is the environment or context of the adolescent. 48% of respondents stating that, with 24% seeing friends smoke, 10.7% see the smoking behavior of parents (father) and 6.6% see the smoking behavior of siblings. Second is the teenagers? desire to know the taste of cigarettes (28%). Then 13.3% of respondents said the affective factor of cigarette smoking plays a role in their behavior. Next is a factor of image formation (10.7%), with 8% of respondents who felt a mature image and show maturity by smoking. At the age of early adolescence (11-15 years) who were most responsible factor is to know the taste of cigarettes while in the middle adolescents (15-18 years) the most dominant factor is to see a friend smoking.